Potret Tiga Pilar Keamanan Pangan di Provinsi Riau - Nizmi, Yusnarida Eka; Wahyudi, Herry; Triono, Triono; Hasibuan, Ahmad Ibrahim Roni Surya; Yulia, Rahmi; Takwa, Tuah Kalti (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2024)
This article will analyze the three pillars of food security in Riau Province and the factors that influence the fulfillment or non-fulfillment of these pillars. It will also outline the impact on vulnerable groups such as women and children if food security is not met. This research employs a qualitative method with data collection through literature analysis and selected documents such as journals, annual reports, and official documents released by governmental or non-governmental agencies. Speaking of factors influencing food security, there are four determining factors: government, economic access, environment, and global/international conditions. However, for food security in Riau, poverty and the environment are the two determining factors and are the main priorities for analysis in this article, including how the Riau Provincial Government responds to these conditions. The article demonstrates that in the pillar of food availability, the quantity and consumption of food are determining factors that impact the occurrence of malnutrition, undernutrition, and even stunting in children. Poverty and the environment are the main determinants of unmet food security in the pillar of food access, with the environmental factors being influenced by deforestation and population growth. Meanwhile, in the pillar of food utilization, the amount of energy consumption is the determining element.